1995
DOI: 10.1006/viro.1995.1455
|View full text |Cite
|
Sign up to set email alerts
|

Neuraminidase Is Essential for Fowl Plague Virus Hemagglutinin to Show Hemagglutinating Activity

Abstract: When hemagglutinin (HA) of fowl plague virus (FPV) was expressed in CV-1 cells by a simian virus 40 vector, hemadsorption was barely detectable, although HA was exposed at the cell surface. However, treatment of HA-expressing cells with Vibrio cholerae neuraminidase (VCNA) resulted in extensive hemadsorption. VCNA treatment enhanced the electrophoretic mobility of the HA1 subunit of HA, indicating the removal of sialic acid. When two oligosaccharides in the vicinity of the receptor binding site of FPV HA were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
67
0
5

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 0 publications
7
67
0
5
Order By: Relevance
“…It may therefore seem surprising that mutations preventing the attachment of an oligosaccharide at either one or both sites had no obvious (Wieringa, 2003) have hypothesized, the multimeric complex composed of the minor proteins functions in targeting and cell entry. As has been shown by Ohuchi et al (1997) for the influenza virus HA protein, the N-glycans adjacent to the receptor binding site can control the receptor affinity of the virus. Another level at which the GP 2a -linked sugars might act is the immune system.…”
Section: Discussionmentioning
confidence: 91%
“…It may therefore seem surprising that mutations preventing the attachment of an oligosaccharide at either one or both sites had no obvious (Wieringa, 2003) have hypothesized, the multimeric complex composed of the minor proteins functions in targeting and cell entry. As has been shown by Ohuchi et al (1997) for the influenza virus HA protein, the N-glycans adjacent to the receptor binding site can control the receptor affinity of the virus. Another level at which the GP 2a -linked sugars might act is the immune system.…”
Section: Discussionmentioning
confidence: 91%
“…Amino acid sequence analysis has revealed that there is considerable variation in both the number and location of potential glycosylation sites among different HA subtypes and even among variants from a single subtype (Chen et al, 2012;Wang et al, 2009). In contrast, the oligosaccharides attached to the upper globular domain at variable sites of the HA molecule have been shown to modulate antigenic properties (Skehel et al, 1984;Wang et al, 2009Wang et al, , 2010bZhang et al, 2015), receptor binding (Gao et al, 2009;Liao et al, 2010;Matrosovich et al, 1999;Ohuchi et al, 1997a;Wang et al, 2010b), and resistance to collectins (Hartshorn et al, 2008;Reading et al, 2009;Tate et al, 2011). The conserved glycosylation sites are located within the stem region of the HA molecule, which has been assumed to provide the main forces that stabilize the HA trimer (Liao et al, 2010;Wiley & Skehel, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…An increase in the receptor-binding activity of HA, as observed after coexpression of NA from simian virus 40 vectors (Ohuchi et al, 1995), could not be clearly recognized. The low receptor-binding activity in the vaccinia virus system may be explained by the relatively high cytopathogenic effect of the vaccinia virus vector and by shedding of HA1 into the medium when using this expression system (Roberts et al, 1993).…”
mentioning
confidence: 88%
“…This concept was further supported by the observation that an NA-minus mutant of influenza virus is still infectious but produces progeny virus only in the presence of exogenously added bacterial NA (Liu & Air, 1993). Furthermore, removal of terminal neuraminic acid by viral NA is important for full receptor binding and fusion activity of haemagglutinin (HA) (Ohuchi et al, 1995). Influenza NAs of subtype N9 and also fowl plague virus (FPV) N1 NA display a second biological activity with unknown function which results in binding of erythrocytes (Laver et al, 1984 ;Hausmann et al, 1995).…”
Section: Introductionmentioning
confidence: 98%